Conference Report on "Disrupted Identities in the Light of Post-Everything" (KULT_online, 2024)
The question of what identities are, how we conceive of them, and how to use them analytically has long perplexed academic thought. In the quest to engage with identity studies, the Research Area 6: Cultural Identities of the International Graduate Centre for the Study of Culture (GCSC) decided to examine not only shifting or changing identities—which may often presuppose some form of continuity—but also identities that are disrupted, severed, or newly (re)shaped. In this vein, the international conference “Disrupted Identities in the Light of ‘Post-Everything’” took place in Giessen from May 14 to 16, 2024. It was organized by Morteza Azimi, Erzhena Dugarova, Farouk El Maarouf, Sandra Engels, and Anastasiia Marsheva. The conference aimed to create a platform for discussing the evolving landscape of identity studies with a particular focus on articulations of disrupted identities within the context of the increasing influence of post-concepts. It also aimed at addressing how drastic events such as wars, regime changes, and forced migration have a disruptive impact on identity constructions.